38.4k views
4 votes
Your answer should be a polynomial in standard form.(x−3) (x−4) =

User Deseosuho
by
5.0k points

2 Answers

7 votes

Answer:

x^2−7x+12

Explanation:

Use the FOIL method: (a+b)(c+d)= ac+ad+bc+bd.

x^2−4x−3x+12

Collect like terms.

x^2 +(−4x−3x)+12

Simplify.

anddthe answer is

x^2−7x+12

User Maxim Suponya
by
4.9k points
3 votes

Answer:

x² - 7x + 12

Explanation:

Use FOIL method

(x - 3) (x -4) = x*x + x *(-4) + (-3)*x + (-3)*(-4)

= x² - 4x - 3x + 12 {Combine like terms}

= x² - 7x + 12

User Xxi
by
4.0k points